A Single Center Retrospective Study of the Impact of COVID-19 Infection on Immune-related Adverse Events in Cancer Patients Receiving Immune Checkpoint Inhibitors. Issue 9 (5th November 2022) - Guo, Mengni; Liu, Jieying; Miao, Ruoyu; Ahmed, Zohaib; Yu, James; Guan, Jian; Ahmad, Sarfraz; Zhou, Shuntai; Grove, Angela; Manoucheri, Manoucher; Socinski, Mark A.; Mekhail, Tarek
Abstract : Immune checkpoint inhibitors (ICIs) can cause a variety of immune-related adverse events (irAEs). The coronavirus disease 2019 (COVID-19) is associated with increased amounts of pro-inflammatory cytokines, which may affect the outcome of irAEs. Data are limited regarding the impact of COVID-19 on irAEs in ICI-treated cancer patients. Hence, in this study, we retrospectively analyzed ICI-treated adult patients with malignant solid tumors at a single institution between August 2020 and August 2021. Patients who had the most recent ICI treatment over 1-month before or after the positive COVID-19 test were excluded from the study. For the COVID-19 positive group, only the irAEs that developed after COVID-19 infection were considered as events. A total of 579 patients were included in our study, with 46 (7.9%) in the COVID-19 positive group and 533 (92.1%) in the COVID-19 negative group. The baseline characteristics of patients in the 2 groups were similar. With a median follow-up of 331 days (range: 21–2226), we noticed a nonsignificant higher incidence of all-grade irAEs in the COVID-19 positive group (30.4% vs. 19.9%, P =0.18). The incidence of grade 3 and 4 irAEs was significantly higher in the COVID-19 positive group (10.9% vs. 3.2%, P =0.02). Multivariate analysis confirmed the association between COVID-19 infection and increased risk of severe irAE development (odds ratio: 1.08, 95% confidence interval: 1.02–1.14, P =0.01). Our study suggested that COVID-19 may pose a risk of severe irAEs in cancer patients receiving ICIs. Close monitoring and possibly delaying ICI administration could be considered when cancer patients are infected with COVID-19.